The relationship between inflation and unemployment in the USA in the surplus approach - Luciano Alencar Barros (Atlantic Review of Economics (ARoEc), 2022)
This article aims to analyze the relationship between inflation and unemployment in the United States, in the 1960s and 2010, from the surplus approach. The objective is to compare this relationship in these two decades, which end with low unemployment rates, to understand the scenario of the American economy till the beginning of 2020, in which historically low unemployment and inflation rates were observed, although at the cost of high inequality.
Keywords: E31; N12; P16; 330; Macroeconomics; Political Economy; Phillips Curve; Surplus Approach; US Economy